Slurry Transport Fundamentals, A Historical Overview & The Delft Head Loss & Limit Deposit Velocity Framework - Miedema, Sape A. (Open textbook library., 2019)
In dredging, trenching, (deep sea) mining, drilling, tunnel boring and many other applications, sand, clay or rock has to be excavated.The book covers horizontal transport of settling slurries (Newtonian slurries). Non-settling (non-Newtonian) slurries are not covered.